Cui dono lepidum novum libellum : Dedicating Latin Works and Motets in the Sixteenth Century - Bossuyt, Ignace (Book collections on Project MUSE., 2008)
During the sixteenth century, the traditional act of dedicating a text took on a new meaning due to the wider dissemination of the printed book. As the dedication and other paratexts thus became an almost indispensable part of the publication, they merit careful examination by those who study the presentation and impact of any printed work in its context. Paratexts bridge the gap between the outside World of the reading public and the enclosed world of the book, and often present biographical information concerning the persons involved in the making of the book. In the present volume, general.